Cost benefits analysis in government project appraisal - Abdul Ghani, Roseziahazni; Abu Samah, A’tiqah Rashidah; Baharuddin, Nurul Syuhada; Mohamad, Zuraida (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
COST BENEFIT ANALYSIS (CBA) is a crucial method for assessing investments in projects or programs involving the public interest. CBA analysis aims to provide preliminary information (in terms of economic parameters) for decision makers in determining the possibility of non-monetary profit projects such as flood mitigation projects, considering the creation of an industrial park to spur economic growth and jobs, and turning a forest into a palm oil plantation. Despite having very little financial resources, the government must conduct many initiatives or projects. They must therefore be used more effectively, that is, in accordance with specified standards considering the social and economic objectives of society. Using CBA, the government guarantees that economic resources are used effectively by choosing ventures that adhere to efficiency standards, (Volden, 2019).